DEVELOPMENT OF MANGROVE ECO-LITERACY STORYTELLING AS ENVIRONMENTAL EDUCATION LEARNING MEDIA FOR COASTAL CHILDREN IN BANTEN - Novi Utami Rosyid (Universitas Sebelas Maret (UNS), 2020)
One of the ecological problems on the Serang Coast is the degradation of mangrove ecosystems. Coastal communities suffer various losses due to damage to mangrove ecosystems. Mangrove degradation is triggered by the people's ignorance in utilizing mangrove ecosystems in a sustainable manner. for this reason, preventive solutions through environmental education are needed to increase the understanding of coastal communities about importance of the mangrove ecosystems through eco-literacy. Eco-literacy is environmental education approach to increase the ecological awareness of the community and create an environmental balance. This study aims to create and develop mangrove eco-literacy storytelling as learning media of environmental education for coastal children at SDN Lontar 2 – Serang. The research method used Research and Development by Borg and Gall (2008). The result of this study was learning media for the mangrove eco-literacy storytelling which has been through feasibility testing and field trials. The feasibility testing resulted 83.34 % with a very good category. Field trials showed that there was a significant effect with the pretest and post-test based on the t-test 0.02 < p = 0.05 which means that users of mangrove eco-literacy storytelling influences to increase of mangrove eco-literacy students. The conclusions show that eco-literacy of mangrove storytelling media is very feasible to use for the learning process and mangrove eco-literacy storytelling is proven to be able to improve the ability of eco-literacy mangroves of students in environmental theme learning at SDN Lontar 2 - Serang.